2015
DOI: 10.1080/01691864.2015.1037793
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level control architecture for the bionic handling assistant

Abstract: The Bionic Handling Assistant is one of the largest soft continuum robots and very special in being a pneumatically operated platform that is able to bend, stretch, and grasp in all directions. It nevertheless shares many challenges with smaller continuum and other softs robots such as parallel actuation, complex movement dynamics, slow pneumatic actuation, non-stationary behavior, and a lack of analytic models. To master the control of this challenging robot, we argue for a tight integration of standard analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…In addition to neural networks, the most basic form of ML algorithm, the global Jacobian can also be obtained using advanced forms of ML algorithms such as linear function approximators, [ 272 ] constrained extreme learning machines, [ 273 ] and ensembles of neural networks. [ 274 ] The mapping of the virtual global Jacobian can be obtained by performing gradient descent over the actuator configuration with the desired position as the target without deducting any models in robotics.…”
Section: Control Implementationmentioning
confidence: 99%
“…In addition to neural networks, the most basic form of ML algorithm, the global Jacobian can also be obtained using advanced forms of ML algorithms such as linear function approximators, [ 272 ] constrained extreme learning machines, [ 273 ] and ensembles of neural networks. [ 274 ] The mapping of the virtual global Jacobian can be obtained by performing gradient descent over the actuator configuration with the desired position as the target without deducting any models in robotics.…”
Section: Control Implementationmentioning
confidence: 99%
“…While the challenge of controlling the segments lengths by supplying the air chambers with appropriate pressures has been addressed in previous work [ 23 , 26 ], this paper focuses on the kinematic control of the end effector. The autonomous exploration of a direct inverse model for controlling the end effector has been accomplished in [ 7 ] where the main emphasis was to start model learning from very limited prior knowledge about the plant.…”
Section: Hybrid Forward Kinematics For a Soft Robotmentioning
confidence: 99%
“…The trout fin was used as the gripper in the front end. Its structure was simple, reliable and easy to use (Rolf and Steil 2013;Rolf et al 2015;Mahl et al 2014). Inspired by the tentacles of octopus, Pi et al reported a flexible three-finger gripper for grasping apples (Pi et al 2021).…”
Section: Introductionmentioning
confidence: 99%